(untitled) (CIPEEX, 2022)
INTRODUCTION: THE MOBILE EMERGENCY CARE SERVICE (SAMU) IS RESPONSIBLE FOR PRE-HOSPITAL CARE, WORKING WITH A QUALIFIED MULTIDISCIPLINARY TEAM. THERE IS A HIGHER PREVALENCE OF OCCUPATIONAL STRESS AND, CONSEQUENTLY, BURNOUT SYNDROME AMONG THESE PROFESSIONALS AND TAKING INTO ACCOUNT THE PANDEMIC OF THE NEW CORONAVIRUS, THERE IS A WORSENING IN THE MENTAL HEALTH OF THESE HEALTH WORKERS. OBJECTIVE: TO DETERMINE THE PREVALENCE OF OCCUPATIONAL STRESS AND BURNOUT SYNDROME IN PREHOSPITAL CARE PROFESSIONALS DURING THE COVID-19 PANDEMIC. METHODOLOGY: FOR THAT, THERE IS A CROSS-SECTIONAL ANALYTICAL STUDY CARRIED OUT WITH THE MULTIDISCIPLINARY TEAM OF SAMU IN THE CITY OF ANÁPOLIS, GOIS, WITH A POPULATION OF ABOUT 110 WORKERS. THE FOLLOWING VALIDATED AND PRE-TESTED QUESTIONNAIRES WERE APPLIED: CUESTIONARIO PARA LA EVALUACIÓN DEL SYNDROME DE QUEMARSE POR EL TRABAJO (CESQT) AND LIPP’S STRESS SYMPTOMS INVENTORY (ISSL). THE RESULTS WERE ANALYZED USING DESCRIPTIVE AND ANALYTICAL STATISTICS WITH A SIGNIFICANCE LEVEL OF 95%. RESULT: REGARDING STRESS IN THE LAST MONTH, THE PREVALENCE WAS HIGHER AMONG FEMALES. IN ADDITION, THE RESEARCH SHOWED THAT THERE WAS AN ASSOCIATION BETWEEN STRESS IN THE LAST MONTH AND AGE GROUP, AND REGARDING MARITAL STATUS, THERE WAS A RELATIONSHIP WITH STRESS IN THE LAST THREE MONTHS. FINALLY, IT WAS POSSIBLE TO OBSERVE AN ASSOCIATION BETWEEN THE NUMBER OF CHILDREN AND STRESS IN THE LAST MONTH. WITH REGARD TO THE BURNOUT SYNDROME, THERE WAS SIGNIFICANCE WITH THE VARIABLES SEX, MARITAL STATUS AND ROLE IN THE SAMU. CONCLUSION: IT IS CONCLUDED, THEREFORE, THAT OCCUPATIONAL STRESS IN THE SAMU DURING THE PANDEMIC PERIOD IS RELATED TO THE SOCIODEMOGRAPHIC PROFILE, FUNCTION PERFORMED AND TIME OF EXERCISE IN THE SAMU. FURTHERMORE, RELATED TO THE PREVALENCE OF BURNOUT SYNDROME, AN ASSOCIATION WAS IDENTIFIED BETWEEN THE SOCIODEMOGRAPHIC PROFILE AND THE FUNCTION PERFORMED. FINALLY, THE IMPORTANCE OF THIS STUDY IS EMPHASIZED, AS THIS THEME IS INNOVATIVE, SINCE FEW RESEARCHES RELATED TO THE SUBJECT WERE FOUND.